GONGO Structure, Risk Transfer, and Waste in Iranian Public Libraries: An Exploratory Study - Shaghaghi Mehdi; Azimi Ali (Libri)
We investigated undermining practices in the Iran Public Libraries Foundation (IPLF) using grounded theory and the concept of “risk society” and “politics of waste”. We interviewed 81 IPLF employees and identified undermining practices in four categories: Normalization, GONGO (Government-Organized Non-Governmental Organization) Structure, High-profile Showcasing, and Inequality. We have argued that pursuing the goal of “normalization” has led authorities to use a centralized and at the same time decentralized form of management. This form of management has caused inefficiencies that have made the managerial restructuring of the organization difficult. As a result, the authorities have abandoned the structural reform and focused on improving the external image of public libraries through media and cultural activities.